A study on problems affecting import movements via full container load (FCL). Case study : Green Peninsula Agencies / Ida Kesumawati Salekan - Salekan, Ida Kesumawati (Faculty of Business and Management, 1997)
The objectives of this exercise is to study the efficiency and effectiveness of import movement FCL container within port area until MA available status. Also to study the problems that arise towards the movement of GPA's container Personal interviews and observations are made to gather the data. From the findings, it was found that there was problems due to increase in operational cost, problems regarding the availability and reliability of prime movers, surplus of containers at Port Klang and "turn around time" of each container. Based on the problems occurred, some recommendations is made in order to establish a more efficient, effective and systematic in movement of GPA's container.